Case report: Eosinophilic fasciitis induced by pembrolizumab with high FDG uptake on 18F-FDG-PET/CT - Amrane, Karim; Le Meur, Coline; Thuillier, Philippe; Alemany, Pierre; Niel, Clémence; Renault, David; Abgral, Ronan (Frontiers in Medicine, 2022)
Eosinophilic fasciitis (EF) is a rare connective tissue disorder causing inflammation and fibrosing of fascia. In this study, we present a very rare case of an immune checkpoint inhibitor (ICI)-induced EF revealed by 18F-fluorodesoxyglucose positron emission tomography (FDG-PET/CT) 20 months after the initiation of Pembrolizumab treatment of a relapsed non-small cell lung cancer (NSCLC). This study presents a 52-year-old Caucasian woman clinically presenting asthenia, inflammatory muscle, and joint pain associated with subcutaneous nodules and symmetrical edema of the lower limbs. Iterative 18FDG-PET/CT scans allow us to guide the therapeutic strategy due to this atypical ICI adverse event.